(untitled) (Iter, 2022)
Classical Greek philosophy does not elabórate a specific theory on Beauty. but rather develops the concept through relation to love. The socratic doctrine that Plato outlines in T h e B an q u e t details most completely this idea. The current of affection and shared love between lover and loved brings about the questions: from what circumstance arises said dynamic? According to Sócrates, love is. at its most basic level. a desire for the loved. That is to say. a desire for the Beauty that is present in the loved. Love in nothing other than love for Beauty. The lover the loved because he perceives in him the vestiges of ideal Beauty.